2002
DOI: 10.1021/bm0255490
|View full text |Cite
|
Sign up to set email alerts
|

Cell Interactions with Polyelectrolyte Multilayer Films

Abstract: The short-term interactions of chondrosarcoma cells with polyelectrolyte multilayer films built up by the alternate adsorption of poly(L-lysine) (PLL) and poly(L-glutamic acid) (PGA) was studied in the presence and in the absence of serum. The films and their interaction with serum proteins were first characterized by means of optical waveguide lightmode spectroscopy, quartz crystal microbalance, and zeta potential measurements. In a serum-containing medium, the detachment forces measured by the micropipet tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
232
0
3

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(245 citation statements)
references
References 50 publications
10
232
0
3
Order By: Relevance
“…Layer-bylayer deposition provides an alternative strategy to fine tune the surface properties of polymeric scaffolds on the nanometer scale [182][183][184]. Recent studies demonstrate that one can easily control the cell behaviors on these self-assembled multilayers by simple manipulation of the deposition process [185][186][187][188][189][190]. However, polyelectrolyte multilayer studies are limited to planner surfaces and spherical particles.…”
Section: Nanofibrous Scaffolds By Electrospinningmentioning
confidence: 99%
“…Layer-bylayer deposition provides an alternative strategy to fine tune the surface properties of polymeric scaffolds on the nanometer scale [182][183][184]. Recent studies demonstrate that one can easily control the cell behaviors on these self-assembled multilayers by simple manipulation of the deposition process [185][186][187][188][189][190]. However, polyelectrolyte multilayer studies are limited to planner surfaces and spherical particles.…”
Section: Nanofibrous Scaffolds By Electrospinningmentioning
confidence: 99%
“…Samples of K 170 L 30 hydrogels were found to be stable and remained transparent in these media, which was somewhat surprising, since they contain numerous multivalent ions and anionically charged proteins. It is likely that the proteins coat the polylysine segments in the gel since it is known that polylysine homopolymer will complex with many serum proteins in solution [107]. Apparently, the resulting polyelectrolyte complexes retain enough charge or hydrophilicity to solubilize the hydrophobic gel scaffold and prevent precipitation and collapse of the network.…”
Section: Copolypeptide Hydrogelsmentioning
confidence: 99%
“…More recently, we found that the cell mobility rate is increased initially along with the increase in poly (ethylene glycol) (PEG) amount on the surface, and reaches maximum values at a moderate grafting mass between 300 and 500 ng cm 22 [16]. Among the various surface engineering methods, the layer-by-layer assembly, refined by Decher in the 1990s [17], can be diversely used to tailor substrate properties and is particularly suitable to address material -cell interactions [18,19]. For example, different deposition parameters of the polyelectrolyte multilayers (PEMs), such as the type of polyelectrolytes [20,21], temperature [22], pH [23] and salt concentrations [24,25], have great impacts on hydration, swelling and mobility of the polymer chains.…”
Section: Introductionmentioning
confidence: 99%